Ordinal and cardinal measures of health inequality: An empirical comparison - David Madden (University College Dublin, UCD School of Economics, 2008)
When measuring health inequality using ordinal data, analysts typically must choose between indices specifically based upon ordinal data and more standard indices using ordinal data which has been transformed into cardinal data. This paper compares inequality rankings across a number of different approaches and finds considerable sensitivity to the choice between ordinal and cardinal based indices. There is relatively little sensitivity to the ethical choices made by the analyst in terms of the weight attached to different parts of the distribution.
hdl:10197/760
Keywords: D63; I18; I31; 330; Inequality; cardinal; ordinal